2008
DOI: 10.1111/j.1750-3841.2008.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Volatile Compounds Produced by 2 Strains of Lactococcus lactis Isolated from Leben (Tunisian Fermented Milk) Using Solid‐Phase Microextraction‐Gas Chromatography

Abstract: The volatile compounds that characterize Leben during fermentation with 2 Lactococcus lactis strains (SLT6 and SLT10) in flasks, in a 100-L fermentor, and during storage at 4 degrees C, were investigated and compared to those from commercial Leben. Volatile compounds from Leben were concentrated by a Carboxen-PDMS fiber and analyzed by GC-MS. These compounds include acids, alcohols, aldehydes, ketones, sulfur compounds, and hydrocarbons. Commercial Leben presented a poor volatile profile compared to the labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
(31 reference statements)
1
20
0
Order By: Relevance
“…Acetaldehyde, converted by threonine aldolase, was not found in this study for unclear reasons. According to the concerned references, milk constituents (Erkaya and Sengul 2011), starter cultures (Ziadi et al . 2008; Routray and Mishra 2011), fermentation course (Routray and Mishra 2011) and storage (Ziadi et al .…”
Section: Resultsmentioning
confidence: 99%
“…Acetaldehyde, converted by threonine aldolase, was not found in this study for unclear reasons. According to the concerned references, milk constituents (Erkaya and Sengul 2011), starter cultures (Ziadi et al . 2008; Routray and Mishra 2011), fermentation course (Routray and Mishra 2011) and storage (Ziadi et al .…”
Section: Resultsmentioning
confidence: 99%
“…Both strains were identified as L. lactis ssp. lactis by 16S ribonucleic acid (RNA) sequencing (Ziadi et al, 2008).…”
Section: Strains and Growth Conditionsmentioning
confidence: 99%
“…Two strains of L. lactis (SLT6 and SLT10) isolated from traditional Tunisian Leben produced the typical (specific) Leben flavour in fermented milk (Ziadi, Wathelet, Marlier, Hamdi, & Thonard, 2008). A preliminary study showed that during growth in milk, these strains produced 35 volatile compounds from the following chemical families: ketones, acids, aldehydes, sulphur compounds and hydrocarbons (Ziadi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[9] Method of solid-phase microextraction and GC-MS with such advantages of being simple, convenient, quick, highly selective, and sensitive, [10,11] thus been widely used in identification of the volatile compounds in yogurt. This study was intended to prepare hickory yogurt with hickory nut and reconstituted milk, and examine its antioxidant activity and volatile flavor compounds.…”
Section: Introductionmentioning
confidence: 99%